Answer:
8n+2 first let’s plug in n which is 1
8(1)+2=10
The answer is 10 but Brian said the expression is equal to 83. He is incorrect because 8 times 1 is 8 and then plus 2 is 10.
I hope it helps.
Answer:
<span>=3<span>√6</span>−3<span>√5</span></span>
Explanation:
<span>3<span><span>√5</span>+<span>√6</span></span></span>
We rationalise the denominator by multiplying the expression by the conjugate of the denominator. <span><span>√5</span>−<span>√6</span></span>
<span><span>3⋅<span>(<span>√5</span>−<span>√6</span>)</span></span><span><span>(<span>√5</span>+<span>√6</span>)</span>⋅<span>(<span>√5</span>−<span>√6</span>)</span></span></span>
<span>=<span><span>3⋅<span>(<span>√5</span>)</span>+3⋅<span>(−<span>√6</span>)</span></span><span><span>(<span>√5</span>+<span>√6</span>)</span>⋅<span>(<span>√5</span>−<span>√6</span>)</span></span></span></span>
<span>=<span><span>3<span>√5</span>−3<span>√6</span></span><span><span>(<span>√5</span>+<span>√6</span>)</span>⋅<span>(<span>√5</span>−<span>√6</span>)</span></span></span></span>
<span>Applying identity
<span><span>(a+b)</span><span>(a−b)</span>=<span>a2</span>−<span>b2</span></span> to the denominator.</span>
<span>=<span><span>3<span>√5</span>−3<span>√6</span></span><span><span><span>(<span>√5</span>)</span>2</span>−<span><span>(<span>√6</span>)</span>2</span></span></span></span>
<span>=<span><span>3<span>√5</span>−3<span>√6</span></span><span>5−6</span></span></span>
<span>=<span><span>3<span>√5</span>−3<span>√6</span></span><span>−1</span></span></span>
<span>=−3<span>√5</span>+3<span>√6</span></span>
<span>=3<span>√6</span>−3<span>√<span>5
</span></span></span>
Answer:
Sunil = 10 and Sushil= 40
Step-by-step explanation:
Present ages-
Sushil= 4x
Sunil= x
5 years ago-
Sushil = 4x - 5
Sunil = x - 5
4x - 5 = 7(x - 5) = 4x - 5 = 7x - 35
= -5 = 3x - 35
= 30 = 3x
= 10 = x
So substitute the xs for 10-
Present Sushil= 4 x 10 = 40
Present Sunil= 10
Step-by-step explanation:
Given: and
We can solve for f(x) by writing
Let
Then
We know that f(0) = 0 so we can find the value for k:
Therefore,
Well since the triangle is split into 2 triangles and they both are the same size so BD on the bottom is 15 which means naturally BC must be 30. Five I'm not sure about